A proposed new pressure vessel design class. (March 2016) - Frith, Robert; Stone, Mark
Abstract: Leveraging off riveted pressure vessel design methods, a factor to account for the likelihood of defects in a partial volumetric inspected weld was introduced into the design approach for welded vessels. This approach is universally adopted in all known pressure equipment codes around the world. Of interest is the use of 0.7 and 0.85 weld efficiency factor for a weld having no volumetric inspection and partial volumetric inspection respectively. To the authors' best knowledge, these have gone unchallenged for the past 88 years. This paper gives the historical background to how these weld efficiencies were developed. The statistical significance of partial volumetric inspection is explored, considering the implications on the safety of the design. The comparative safety of partially volumetrically inspected welds and non-volumetrically inspected welds is challenged. A proposal is made for the introduction of a new design class based on a fabricator nominated weld efficiency and hydrostatic pressure testing to near yield conditions without volumetric inspection. While the paper is not conclusive in its findings, its purpose is to challenge the understanding of weld efficiencies and to encourage new developments.